2001
DOI: 10.1046/j.1464-410x.2001.02029.x
|View full text |Cite
|
Sign up to set email alerts
|

The modified Koyanagi repair for severe proximal hypospadias

Abstract: Objective To report the method and results of a modi®ed one-stage Koyanagi repair (urethroplasty with a parameatal-based and fully extended circumferential foreskin¯ap) to preserve the vascularity to the peripheral portion of the neourethra, in the repair of severe hypospadias. Patients and methods Using a skin-incision line as in the original Koyanagi repair, a circumferential incision is made < 5 mm proximal to the corona and the urethral plate incised as for repair of chordee. A Ushaped skin incision is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…In the armamentarium of techniques used to reconstruct proximal severe hypospadias, the Koyanagi procedure [4] and its variant e the Hayashi procedure [5] e are established alternatives for urethral reconstruction. The aim of this article is to compare the outcomes of these two techniques and discuss their place compared to other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the armamentarium of techniques used to reconstruct proximal severe hypospadias, the Koyanagi procedure [4] and its variant e the Hayashi procedure [5] e are established alternatives for urethral reconstruction. The aim of this article is to compare the outcomes of these two techniques and discuss their place compared to other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The glans is drawn dorsally through a button-hole in the dartos pedicle bringing the neourethra ventrally. These two modifications, the island flap and loop shape, are the modifications described later by Hayashi et al [9] In the report by Snow and Cartwright the neourethra is drawn through the tip of the glans whilst in the Hayashi description the glans is split. [20] In this regard the technique we use corresponds to the latter technique.…”
Section: Discussionmentioning
confidence: 95%
“…Different techniques were performed: The Koyanagimodified Hayashi procedure, [9] the tubularised transverse preputial island flap technique (Duckett), [10] the onlay preputial island flap urethroplasty, [11] the augmented Duckett (Duckett + Thiersch-Duplay), [12] and a simple tubularised plate urethroplasty without plate incision. The decision to transect the urethral plate was taken by the surgeon based on his preoperative judgment of the severity of the chordee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of their patients underwent third and fourth surgeries [30,31]. Complication rates have been as high as 30% and consist of meatal stenosis and fistulae [32][33][34]. Glassberg et al [35] modified the procedure and reported a fistula rate of 50%.…”
Section: Introductionmentioning
confidence: 99%